Engineering a better light sheet in an axicon‐based system using a flattened Gaussian beam of low order. Issue 6 (25th February 2022) - Saghafi, Saiedeh; Becker, Klaus; Gori, Franco; Foroughipour, Massih; Bollwein, Christine; Foroughipour, Meraaj; Steiger, Katja; Weichert, Wilko; Dodt, Hans‐Ulrich
Abstract: Lasers are fundamental tools in research and development. The shape of an incident laser beam directly affects the results, when it propagates through complex structured meso‐aspheric optical elements. In conic‐based systems utilizing elements such as axicons, the impact of secondary lobes is mostly overlooked, although the intensity distributions at the central spot and the side‐lobes directly affect the beam properties. We investigate the interaction of two axicons (160° and 170°) with incident beams approximated by Gaussian, high‐order Flattened‐Gaussian, and low‐order Flattened‐Gaussian functions. We demonstrate that replacing an incident Gaussian beam with a low‐order Flattened‐Gaussian beam reduces the secondary lobes and significantly improves the uniformity of the intensity profile. We practically applied this effect in engineering a conic‐aspheric‐based static light‐sheet microscope producing markedly improved results. Abstract : The shape of an incident laser beam directly affects the results when it propagates through complex structured meso‐aspheric optical elements. In conic‐based systems utilizing elements such as axicons, the impact of secondary lobes is mostly overlooked. We investigate the interaction of two axicons (160° and 170°) with incident beams approximated by Gaussian, high‐order Flattened‐Gaussian, and low‐order Flattened‐Gaussian functions. Replacing an incident Gaussian beam with a low‐order Flattened‐Gaussian beam reduced the secondary lobes and significantly improved the uniformity of the intensity profile.